2018
DOI: 10.7717/peerj.6030
|View full text |Cite
|
Sign up to set email alerts
|

Structural plasticity in root-fungal symbioses: diverse interactions lead to improved plant fitness

Abstract: Root-fungal symbioses such as mycorrhizas and endophytes are key components of terrestrial ecosystems. Diverse in trophy habits (obligate, facultative or hemi-biotrophs) and symbiotic relations (from mutualism to parasitism), these associations also show great variability in their root colonization and nutritional strategies. Specialized interface structures such as arbuscules and Hartig nets are formed by certain associations while others are restricted to non-specialized intercellular or intracellular hyphae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 181 publications
(278 reference statements)
0
31
0
Order By: Relevance
“…Ericoid mycorrhizae enhance the fitness and productivity of the Ericaceae plants and play a vital role in their adaptation to soils with low pH and slow turnover of organic matter. Mycorrhizal fungi supply their host plants with nitrogen, phosphate, and other nutrients, which are mobilized via the breakdown of complex organic compounds by fungal exoenzymes (Kariman et al, 2018). Several studies also reported that EM colonization has positive effects on the tolerance of plants to heavy metals (Daghino et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Ericoid mycorrhizae enhance the fitness and productivity of the Ericaceae plants and play a vital role in their adaptation to soils with low pH and slow turnover of organic matter. Mycorrhizal fungi supply their host plants with nitrogen, phosphate, and other nutrients, which are mobilized via the breakdown of complex organic compounds by fungal exoenzymes (Kariman et al, 2018). Several studies also reported that EM colonization has positive effects on the tolerance of plants to heavy metals (Daghino et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The biodiversity of soil bacterial communities alone is enormous where one gram of soil may contain anything from ten thousand to ten million taxa (Gans, Wolinsky & Dunbar, 2005;Torsvik, Ovres & Thingstad, 2002;Tringe et al, 2005). The diversity and roles of microbial symbionts (e.g., N-fixers and mycorrhiza) should not be underestimated as these are key components of many terrestrial ecosystems (Chaia, Wall & Huss-Danell, 2010;Hayat, Ali & Amara, 2010;Kariman, Barker & Tibbett, 2018). The protists are the most diverse group and are single celled eukaryotes.…”
Section: Species Diversitymentioning
confidence: 99%
“…Although the extent of root colonization is a universally recognized index for mycorrhizal development, it does not necessarily reflect the actual mycorrhizal functioning and mycorrhiza-mediated benefits for host plants such as nutrient gain and tolerance against environmental stresses (Jakobsen, 1995; Smith et al, 2004, 2009; Kariman et al, 2014a,b, 2018). To better understand the impact of NPs on mycorrhizas, along with the quantitative measurement of mycorrhizal development (i.e., root colonization), the mycorrhizal benefits for NP-treated plants need to be experimentally investigated.…”
Section: Substrate Propertiesmentioning
confidence: 99%
“…Mycorrhizal and rhizobial symbioses, arguably the most important symbioses on earth, are indispensable functional guilds of terrestrial ecosystems and continue to play a vital role in soil nutrient cycling, mineralization of organic matter, shaping plant and microbial communities, and ultimately safeguarding the functionality and resilience of the ecosystems (Finlay, 2008; van der Heijden et al, 2008). To date, a multitude of beneficial root-fungal symbioses have been described based on the properties of interface structures and the plant-fungus species involved (Smith and Read, 2008; Kariman et al, 2018). In the nanotechnology context, however, most research has primarily focused on the ubiquitous mycorrhiza i.e., arbuscular mycorrhiza, with a few studies partially dealing with other associations.…”
Section: Introductionmentioning
confidence: 99%